ANALISIS AWAL KESTABILAN PONTON KAPAL ISAP PASIR KEDALAMAN 40 M - Rosa, Firlya (Mesin, 2015)
AbstractMining of material on the sea ussualy use a suction dredgers and vessels such as suction dredges of sand. The suction dredge can be modified for mining of tin, that is known Kapal Isap Prod uksi (KIP). To change its function, it is necessary to analyze the stability of the pontoon for relocation and repositioning equipment suction dredges for sand into a suction dredge for tin production. Analysis conducted by the surveying, calculate the weight estimate and measure the position of the equipment to determine the reference point and the center point of the mass (COG) by using the moments method. From the analysis it was found that immersion (TPC) pontoon at 5 ton / cm so that pontoon for the su ction dredges for sand that can be modified into a tin cutter suction dredges. Heel to Starboard degrees show that a slope of suction dredge towards the port and righting momen (GZ) can not fulfill the IMO standards.Â Key Word : KIP, COG, IMOÂ AbstrakPenambangan dari dasar laut umumnya menggunakan kapal baik kapal keruk maupun kapal isap seperti kapal isap pasir. Kapal isap pasir dapat dimodifikasi untuk digunakan kapal isap produksi (KIP) timah. Namun, untuk merubah fungsinya, maka perlu dilakukan analisa kestabilan ponton sebagai data awal untuk melakukan relokasi dan reposisi peralatan kapal isap pasir menjadi kapal isap produksi timah. Analisa dilakukan dengan mendata, menghitung berat estimasi dan mengukur posisi peralatan terhadap titik acuan dan menentukan pusat titik massa (COG) dengan menggunakan metode momen. Dari hasil analisa didapatkan bahwa immersion (TPc) ponton sebesar 5 ton/cm sehingga ponton bahwa kapal isap pasir dapat dimodifikasi menjadi kapal isap produksi timah. Kapal mengalami kemiringan ke arah port kapal dan sudut lengan pengembali (GZ) tidak memenuhi standar IMO.Â Kata kunci : KIP, COG, IMO